Adsorption-Hydration Sequence Method for Methane Storage in Porous Material Slurry - Chen, Jun-Li; Xiao, Peng; Zhang, De-Xin; Chen, Guang-Jin; Sun, Chang-Yu; Ma, Qing-Lan; Yang, Ming-Ke; Zou, En-Bao (Frontiers in Chemistry, 2020)
Porous materials are deemed to be capable for promoting hydrate formation, while for the purpose of hydrate-based gas storage, those systems containing porous materials often cannot meet the requirement of high storage density. To increase the storage density, an adsorption-hydration sequence method was designed and systematically examined in this study. Methane storage and release in ZIF-8 slurries and fixed beds were investigated. The ZIF-8 retained 98.62%, while the activated carbon lost 62.17% of their adsorption capacities in slurry. In ZIF-8 fixed beds, methane storage density of 127.41 V/Vbed was acquired, while the gas loss during depressurization accounted for 21.50% of the gas uptake. In the ZIF-8 slurry, the storage density was effectively increased with the adsorption-hydration sequence method, and the gas loss during depressurization was much smaller than that in fixed beds. In the slurry, the gas uptake and gas loss decreased with the decrease of the chilling temperature. The largest gas uptake and storage density of 78.84 mmol and 133.59 V/Vbed were acquired in the slurry with ZIF-8 content of 40wt.% at 268.15 K, meanwhile, the gas loss just accounted for 14.04% of the gas uptake. Self-preservation effect was observed in the slurry, and the temperature for the slowest gas release was found to be 263.15 K, while the release ratio at 10 h reached to 43.42%. By increasing the back pressure, the gas release rate could be effectively controlled. The gas release ratio at 1.1 MPa at 10 h was just 11.08%. The results showed that the application of adsorption-hydration sequence method in ZIF-8 slurry is a prospective manner for gas transportation.